Motor engagement relates to accurate perception of phonemes and audiovisual words, but not auditory words - Kelly Michaelis (Nature Portfolio, 2021)
Michaelis et al. used extra-cranial EEG during a forced-choice identification task to investigate the role of the motor system in speech perception. Their findings suggest that left hemisphere dorsal stream motor areas are dynamically engaged during speech perception based on the properties of the stimulus.